2021
DOI: 10.32866/001c.23573
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Factors and Telework Status in the US during the COVID-19 Pandemic

Abstract: The COVID-19 outbreak posed a considerable risk to the health of people in the US and across the world. To reduce its spread, various companies in America adopted a range of preventive measures, such as telework, for the majority of their workforces. Considering that these measures have disproportionate effects on individuals, this study examined the potential relationship between socioeconomic characteristics and telework status in the United States through mixed logit models developed in this research. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
4
11
1
Order By: Relevance
“…Similar results were reported in a Japanese study conducted by Niu et al (2021). Given that males are often employed in economic sectors, such as construction, where work cannot be done from home, Jiao and Azimian (2021) found that males were less likely to telework.…”
Section: Note(s)supporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported in a Japanese study conducted by Niu et al (2021). Given that males are often employed in economic sectors, such as construction, where work cannot be done from home, Jiao and Azimian (2021) found that males were less likely to telework.…”
Section: Note(s)supporting
confidence: 88%
“…Similarly, a Japanese study found that worker's age was not a statistically significant differentiator for changes in work location (Niu et al, 2021). Yet, pandemic-driven teleworking research found that younger adults under the age of 35 were more likely to be involved in telework (Jiao and Azimian, 2021).…”
Section: Formulation Of Research Hypothesesmentioning
confidence: 98%
“…While the COVID-19 pandemic caused all types of travel to initially fall across many different travel modes, due to stay-at-home orders and other public health restrictions, the declines in travel were greater among higher-income people (Brough et al 2021 ) who were more likely than lower wage workers to work from home (Jiao and Azimian 2021 ). These steep drops in ridership were on top of more gradual patronage declines in the years leading up to the pandemic (Berrebi and Watkins 2020 ; Manville et al 2022 ).…”
Section: Previous Researchmentioning
confidence: 99%
“…Using data from another national survey, Jiao and Azimian ( 2021 ) analyzed responses to the U.S. Census Household Pulse Survey (HPS) to compare travel behaviors in September and October of 2020 with the pre-pandemic era. Their results differed slightly from the findings from the two previously mentioned surveys.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation